Collective Leadership Problems and Solutions in Pesantren-Based School - Nur Rohman (Universitas Negeri Semarang, 2021)
The emergence of the problem of collective leadership in pesantren-based schools is due to the same comparison between authority and responsibility. The purpose of this study was to find out (1) the problems faced in joint leadership in the management of pesantren-based schools. (2) Efforts to solve problems on problems that arise in the joint leadership of the management of pesantren-based schools. This research uses a qualitative approach with a case study research design. The research location is at the Islamic boarding Integrated Superior Junior High School of Bumi Kartini Jepara. Data collection techniques are through in-depth interviews, in-depth observation, and documentation. The analysis technique used is reduction, display and data verification. The results of the study indicate that the problems faced by collective leadership in pesantren-based schools are leadership dualism and differences in viewpoints between school principals and pesantren kyai who both have power. Meanwhile, the principal has a vision, mission, goals and targets that must be realized. Likewise, kyai pesantren also have excellent programs. This polemic burdened students with both programs from schools and pesantren. The difference in understanding of the working hours of the principal and the kyai of the pesantren is a problem. Similarly, the effect of the lack of socialization and the lack of firmness in the schedule and responsibilities of both principal and kyai of pesantren were also found. So the solutions offered include proposing a party who initiates to invite all elements from the management of the Foundation, schools and Islamic boarding schools to intensely and periodically discuss unifying perceptions or points of view and encourage the Foundation management to provide direction and affirmation of responsibilities, especially regarding the duration of working hours for both schools and Islamic boarding schools, as well as ensuring that socialization and intense communication are carried out regarding the schedule for the division of tasks and responsibilities of each by the principal and kyai of pesantren.